Relationship between Oil Prices, Oil Consumption and Financial Development in Developed Countries - Nurgabylov, Murat; Yerzhanova, Saltanat; Sarsenova, Akmaral; Kaltayeva, Saule; Tazhibayeva, Raikhan; Baimbetova, Assel (International Journal of Energy Economics and Policy, 2025)
The aim of this study is to analyze the relationships between financial development, oil prices, and energy consumption in OECD countries over the period 2000–2023. To identify long-run relationships, the Pedroni panel cointegration test is employed, while panel causality analysis is conducted to determine the direction of these relationships. Furthermore, to enhance the reliability of the cointegration results, analyses are carried out using FMOLS and DOLS estimators. The findings reveal a unidirectional causality running from financial development to energy consumption, supporting the conservation hypothesis, which posits that the financial system plays a decisive role in determining energy consumption. Additionally, the results indicate a unidirectional causality from oil prices to energy consumption. The consistency in the direction of the regression coefficients obtained from both FMOLS and DOLS methods confirms the robustness of the results.